Winterwood - Ernshaw, Shea (Simon Pulse, 2019)
"Be careful of the dark, dark wood... Especially the woods surrounding the town of Fir Haven. Some say these woods are magical. Haunted, even. Rumored to be a witch, only Nora Walker knows the truth. She and the Walker women before her have always shared a special connection with the woods. And it's this special connection that leads Nora to Oliver Huntsman -- the same boy who disappeared from the Camp for Wayward Boys weeks ago -- and in the middle of the worst snowstorm in years. He should be dead, but here he is alive, and left in the woods with no memory of the time he'd been missing. But Nora can feel an uneasy shift in the woods at Oliver's presence. And it's not too long after that Nora realizes she has no choice but to unearth the truth behind how the boy she has come to care so deeply about survived his time in the forest, and what led him there in the first place. What Nora doesn't know, though, is that Oliver has secrets of his own -- secrets he'll do anything to keep buried, because as it turns out, he wasn't the only one to have gone missing on that fateful night all those weeks ago. For as long as there have been fairy tales, we have been warned to fear what lies within the dark, dark woods and in Winterwood, author Shea Ernshaw, shows us why."--